Incobotulinum Toxin a Effective in Treating Plantar Fasciitis - Nichols, Emma Hitt (MD Conference Express, 2014)
Up to 2 million patients per year require treatment for plantar fasciitis, with risk factors including prolonged weight-bearing activity, inappropriate shoe wear, greater body weight, and medical comorbidities. This article discusses data from the Treatment of Plantar Fasciitis With Xeomin study [NCT01678001], which evaluated long-term outcomes of patients with plantar fasciitis treated with incobotulinum toxin A.